Shoot, edit, share video production for mass media, marketing, advertising, and public relations - Johnson, Kirsten A. 1974-; Radosh, Jodi (Routledge, Taylor & Francis Group, 2017)
"Shoot, Edit, Share is an interactive, accessible introduction to video production techniques, concepts, and terminology. With the increasing availability of affordable video equipment, many students and professionals need to learn the basics of video production without being overwhelmed by technical details and equipment lists. Covering preproduction, production, editing in post, and distribution, this book shows you how to produce video quickly and effectively for a range of clients, from commercial firms to community service organizations. Key features include: A companion website including video interviews with professionals that demonstrate and reinforce techniques covered in the book; Service-learning exercises that engage readers in real-world learning experiences, encouraging them to interact with their communities and new clients; Clear, easy to follow and heavily illustrated guides for all of the equipment and processes that go into video production; Focus on creating stories for a target audience, and building convincing and engrossing narrative through videos; A thorough breakdown of all the techniques needed in post-production, through editing, well-designed graphics, and quality sound; A best-practices guide to viral videos, sharing video content online and increasing its exposure on social media sites; QR codes throughout the book, that when scanned, demonstrate video techniques and concepts related to what was read."--Publisher description.
"A Focal Press Book"--Cover. - Includes bibliographical references and index. - Print version record
Keywords: Video recordings -- Handbooks, manuals, etc -- Production and direction; Cinematography -- Handbooks, manuals, etc; Television in publicity -- Handbooks, manuals, etc; Vidéo; Production et réalisation; Guides, manuels, etc; Cinéma; Guides, manuels, etc; BUSINESS & ECONOMICS; Industries; Media & Communications; TECHNOLOGY & ENGINEERING; Telecommunications; Cinematography; Television in publicity; Video recordings; Production and direction; Handbooks and manuals